The Role of European Equestrian Institutions in Training Professionals: Outcomes from a Workshop on Horse Welfare in Equestrian Education - Gabriella Torell Palmquist; Nina Känsälä Alveheim; François Huot-Marchand; Lisa Ashton; Victoria Lewis (Animals)
This paper highlights and summarizes the experiences and perceptions of European equestrian educational experts from a workshop held at the French National Riding School in Saumur. The workshop, which brought together fifty leading experts, aimed to address challenges in equestrian education, identify common ground, and share best practices. Using ‘The World Café’ method, the participants were divided into groups to discuss four key topics: the relationship between horses and humans, diversity of perspectives versus common ground, training philosophy, and social acceptability. A follow-up online focus group was conducted six months later, and the discussions were transcribed and analyzed using qualitative content analysis. The results revealed the need for a universal cultural shift towards an evidence-based approach to riding and training horses, with equine welfare at its core. Key challenges, such as anthropomorphism, varying standards across disciplines and countries, and the evolving horse–human relationship, pose risks to the social license to operate. The findings suggest that educational institutions, with their shared values, are well-positioned to lead this change, although further research is needed to address pedagogical challenges. The study also emphasizes the importance of communicating ’good news stories’ to promote evidence-based practices in training and competition.